Combination of Profile Matching and SAW Methods for College KIP Admission - Riya Majalista; M. Izman Herdiansyah; Zaid Amin (Jurnal Riset Informatika, 2022)
The KIP College program at Baturaja University has been running since 2020. The large number of people interested in this program has made the university that runs this program have difficulty making decisions about recipients of the KIP college program. The data is on interested participants in the KIP program studying at Baturaja University (UNBARA). The gap between the quota determined by the Ministry of Education, Culture, Research, and Technology and the number of registrants triggers difficulties for management in making decisions. This research aims to analyze the KIP Kuliah program selection results using the combination of Profile Matching and SAW methods. From the analysis of determining criteria and rankings using the Combination Method of Profile Matching and SAW, the results show the names of students who will occupy the UNBARA KIP program quota. The result of data calculations already obtained a value of 1,96667 with alternative data A208 in the name of Randi. Alternative A208 can be recommended as the recipient of the College KIP because it has the profile most appropriate to the specified criteria. So, it can be concluded that SPK, using the combination of Profile Matching and SAW methods, can be applied as a form of recommendation in decision-making in determining UNBARA KIP college program recipients